Telecommunications technologies : opportunities for developing countries. - BOAKYE, Kwame A. (1995)
Discusses the interplay between telecommunications and socio-economic development. Examines the role of some key technologies, and outlines the potential for their exploitation by developing economies. Presents a proposal of how the technologies may be combined into an architecture for a telecommunications system for a devleoping country, and suggests how the capabilities provided by telecommunications may be most effectively utilized.